Sarconesin: Sarconesiopsis magellanica Blowfly Larval Excretions and Secretions With Antibacterial Properties - Díaz-Roa, Andrea; Patarroyo, Manuel A.; Bello, Felio J.; Da Silva, Pedro I. (Frontiers in Microbiology, 2018)
Larval therapy (LT) is an alternative treatment for healing chronic wounds; its action is based on debridement, the removal of bacteria and stimulating granulation tissue. The most important mechanism when using LT for combating infection depends on larval excretions and secretions (ES). Larvae are protected against infection by a spectrum of antimicrobial peptides (AMPs); special interest in AMPs has also risen regarding understanding their role in wound healing since they degrade necrotic tissue and kill different bacteria during LT. Sarconesiopsis magellanica (Diptera: Calliphoridae) is a promising medically-important necrophagous fly. This article reports a small AMP being isolated from S. magellanica ES products for the first time; these products were obtained from third-instar larvae taken from a previously-established colony. ES were fractionated by RP-HPLC using C18 columns for the first analysis; the products were then lyophilised and their antimicrobial activity was characterised by incubation with different bacterial strains. These fractions’ primary sequences were determined by mass spectrometry and de novo sequencing; five AMPs were obtained, the Sarconesin fraction was characterised and antibacterial activity was tested in different concentrations with minimum inhibitory concentrations starting at 1.2 µM. Potent inhibitory activity was shown against Gram-negative (Escherichia coli D31, Pseudomonas aeruginosa 27853) and Gram-positive (Staphylococcus aureus ATCC 29213, Micrococcus luteus A270) bacteria. Sarconesin has a significant similarity with Rho-family GTPases which are important in organelle development, cytoskeletal dynamics, cell movement and wound repair. The data reported here indicated that Sarconesin could be an alternative candidate for use in therapeutics against Gram-negative and Gram-positive bacterial infections. Our study describes one peptide responsible for antibacterial activity when LT is being used. The results shown here support carrying out further experiments aimed at validating S. magellanica AMPs as novel resources for combating antibacterial resistance.